Hand Gesture Detection Using Segmentation (International Journal of Innovative Research in Computer Science & Technology, 2021)
Hand gesture detection is a project which  recognizes the gesture of hands and detect accordingly.  Hand Gesture recognition is an important technique for  creating user-friendly interfaces. Hand gesture is  recognized by robots, for example, can take human  commands, and those who are deaf or who cannot speak,  can recognize the sign language for communication. Hand  gesture recognition in video games could help by allowing  players to use gestures to interact with the game rather than  a controller. Moreover, to account for the infinite number of  possible hand positions in three dimensions, such an  algorithm must be more robust. It must also be capable of  working with video rather than static images.
Keywords: Gesture; human-computer; segmentation; user interface